Microstructures and wear properties of TiC coating produced by laser cladding on Ti-6Al-4V with TiC and carbon nanotube mixed powders. (27th July 2019) - He, Binfeng; Ma, Dayan; Ma, Fei; Xu, Kewei
Abstract: Titanium carbide (TiC) coatings were fabricated by laser cladding on Ti-6Al-4V alloy with TiC and carbon nanotube (CNT) mixed powders. Scanning electron microscope (SEM) with energy dispersive spectroscopy (EDS), X-Ray diffraction (XRD) and analysis indicate that the coatings mainly consist of TiC, Al3Ti, Ti3AlC2 and VC. Microhardness tester and friction wear testing machine were also used to the tests of the coatings, the results show that the coatings, thickness of about 0.8 mm, surface microhardness of about 2854 HV0.5, have a lower friction coefficient and a much higher wear resistance than the substrate. The wear mechanism of the coating is abrasive wear, the mechanism of TC4 substrate is plastic deformation and plowing grooves.